Potent Antibacterial and Antibiofilm Activities of a Synthetic Remineralizing Preparation of Nano-Hydroxyapatite Against Cariogenic Streptococcus mutans Using an Ex-vivo Animal Model - El-Gar, Yasmeen H. Abo; Etman, Wedad M.; Genaid, Thuraia M.; Al-Madboly, Lamiaa A. (Frontiers in Dental Medicine, 2022)
Aim: evaluate the biocompatibility and antibiofilm actions of two nano-hydroxy apatite (NHA) Methodology: NHA are biomaterials use in direct contact with living tissues. Therefore, they should be tested for their safety beside assessment of their MIC and MBC using broth microdilution method. One hundred and twenty extracted bovine incisors were collected and cleaned to ensure the absence of any defects. Enamel blocks with different size (2×2×3mm) and (5×5×2mm) were prepared from their labial surfaces using an isomet saw. Enamel blocks are used for detecting the suitable concentration will be used in the following experiments using EDX. The remaining enamel blocks divided into 5 equal groups to detect inhibitory effect against bacterial adhesion to the initial enamel caries like lesions using viable count technique beside the antibiofilm activity against mature biofilm of S. mutans using confocal laser microscopy. The remaining enamel blocks were used as a representing data for detect surface topography for each group by using the SEM. Result: The data showed safety of NHA suspensions. Additionally, only NHA suspension of large nanoparticle size (NHA-LPS) had MIC of 12.5 mg/mL against S. mutans. Also, have the higher percentages of Ca and P in the enamel blocks. Furthermore, the lowest level of bacterial adhesion was recorded in (group III) treated by NHA-LPS which was non-significantly different with the positive control group V. Biofilm thickness in group IV treated with NHA-SPS recorded high biofilm thickness followed by group III. Interestingly, group III showed greater killing effect against mature biofilm which is slightly higher than the positive control group V. In group III Surface topography revealed very smooth enamel surface with closed pores. Accordingly, NHA-LPS suspension had antiadhesive, antibacterial and antibiofilm effect against cariogenic S. mutans representing a promising possibility to be recommended for safe effective remineralization.